Anterior segment swept-source OCT in the post-operatory evaluation of patients with medial rectus surgery - Rodrigues, Catarina (2020)
Purpose: Evaluate the Anterior Segment Swept-source Optical Coherence Tomography (AS-OCT) imaging features of medial rectus with previous surgery and to study the association of this features with the surgical plan. Methods: Evaluation of 43 control eyes (Group A) and 25 eyes submitted to medial rectus surgery (Group B). AS-OCT  scans were obtained on lateral gaze at a fixation light. Muscle insertion(MI) was detected using a graphical user interface(GUI) that identifies the corneo-scleral junction automatically and obtain a automatic muscle insertion to corneo-scleral(ML) distance. All algorithms and GUI were built as a unified tool in MATLAB.A receiver operating curve analysis (ROC) was used to identify cutt-off values from eye with previous muscle recession. Results: In group B, 6 eyes were submitted to resection (23,1%), 5 eyes to faden operation (19,2%) and 6 eyes to recession (23,1%) and 8 eyes to a combination of recession and faden operation (34,6%). In group A, the mean ML distance was 5,12mm [+/-0,47mm]. On recession the mean ML distance was 7,50mm [+/- 1,01mm] and we found a strong correlation between the ML distance and the surgical plane (r=0.77; p<0.01). On faden operation the ML distance was not statistically different from Group A (p=0.88). In our resection cohort we verified that ML distance was statistically different from patients in control group (p < 0.01) and non-different from eyes submitted to recession surgery. Conclusion: AS-OCT evaluation of the ML distance have a strong correlation with the surgical plan and may identify with high sensitivity muscles submitted to surgery.